Atypical, milder presentation in a child with CC2D2A and KIDINS220 variants. Issue 1 (January 2020) - Lam, Zena; Albaba, Shadi; Study, DDD; Balasubramanian, Meena
Abstract : With the increasing availability and clinical use of exome and whole-genome sequencing, reverse phenotyping is now becoming common practice in clinical genetics. Here, we report a patient identified through the Wellcome Trust Deciphering Developmental Disorders study who has homozygous pathogenic variants in CC2D2A and a de-novo heterozygous pathogenic variant in KIDINS220 . He presents with developmental delay, intellectual disability, and oculomotor apraxia. Reverse phenotyping has demonstrated that he likely has a composite phenotype with contributions from both variants. The patient is much more mildly affected than those with Joubert Syndrome or Spastic paraplegia, intellectual disability, nystagmus, and obesity, the conditions associated with CC2D2A and KIDINS220 respectively, and therefore, contributes to the phenotypic variability associated with the two conditions.